THE EFFECT OF YOUTUBE MEDIA OF ONLINE REVIEW, VISUALIZATION AND TRUST ON INTENTION TO BUY SMARTPHONE - Ariani Kusumo Wardhani; Dearna Kee June Chen (Universitas Mercu Buana, 2021)
Within the conduct of the study, the research adopted the TAM (Technology Acceptance) theory as the basis for identifying the factors that influence the customers to perform transactions through online sites. Furthermore, within the study as well the researcher would like to adopt the TPB (Theory Planned Behaviour) as the support of TAM theory in predicting the online consumer behaviours within the online sites. On the other hand, in the data analysis the researcher has run by using the PLS 3.0. In the same time, survey by means of questionnaire distribution carried out toward the respondents who used to perform transactions through online sites. Finally, this research found that visualization, online review and trust have positive impact on purchase intention smartphone of consumer through You Tube Channel